Formalising Greenhouse Gas Emissions Reporting Through BPMN: A Process Modelling Approach - Oliveira, D.; Marques, A.; Laureano, Raul M. S. (1st Business Analytics and Data Science International Conference, 2025)
The increasing demand for rigorous and traceable sustainability disclosures, re-inforced by regulatory developments such as the Corporate Sustainability Re-porting Directive (CSRD), has heightened the need to formalize greenhouse gas (GHG) emissions reporting processes. This article proposes a Business Process Model and Notation (BPMN)-based model designed to represent the GHG emissions reporting workflow in a structured and standardized manner, thereby supporting future digitalization and automation efforts. The model was devel-oped based on empirical insights gathered through semi-structured interviews with sustainability professionals from two leading Portuguese companies in their respective sectors. The interviews enabled the identification of core activi-ties, roles, data flows, and decision points, which were then formalized using BPMN 2.0 conventions. The model was perceived by participants as clear, practically relevant, and broadly applicable, despite organizational differences in maturity and data integration practices. While suggestions for refinement were made, namely the inclusion of audit-related subprocesses, additional internal contributors, and references to supporting systems, the model was recognized as a robust and adaptable foundation. Beyond its immediate application, this work contributes to the broader discussion on process modelling in sustainability, highlighting BPMN’s potential as a tool to enhance data traceability, internal coordination, and readiness for regulatory compliance in GHG emissions reporting.